2016
DOI: 10.1177/0741932516644054
|View full text |Cite
|
Sign up to set email alerts
|

Improving Learning for All Students Through Equity-Based Inclusive Reform Practices

Abstract: The present investigation examines the schoolwide applications model (SAM) as a potentially effective school reform model for increasing equity-based inclusive education practices while enhancing student reading and math achievement for all students. A 3-year quasi-experimental comparison group analysis using latent growth modeling (LGM) was used with seven urban elementary or elementary/middle schools and seven matched comparison schools in the same district. Results suggest significantly larger growth for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…The present study is a follow-up to previous research on the effectiveness of the SAM intervention to all students participating in the selected schools. Our earlier findings revealed that math score growth was significantly larger for students in SAM implementation schools than in comparison schools (Choi et al, 2017). Although no significant reading growth difference was observed between implementation and comparison groups, schools that implemented with the highest scores on a measure of fidelity made better improvements on both reading and math while scores of matched comparison schools actually decreased (Choi et al, 2017).…”
Section: Context and Purposementioning
confidence: 82%
See 4 more Smart Citations
“…The present study is a follow-up to previous research on the effectiveness of the SAM intervention to all students participating in the selected schools. Our earlier findings revealed that math score growth was significantly larger for students in SAM implementation schools than in comparison schools (Choi et al, 2017). Although no significant reading growth difference was observed between implementation and comparison groups, schools that implemented with the highest scores on a measure of fidelity made better improvements on both reading and math while scores of matched comparison schools actually decreased (Choi et al, 2017).…”
Section: Context and Purposementioning
confidence: 82%
“…Our earlier findings revealed that math score growth was significantly larger for students in SAM implementation schools than in comparison schools (Choi et al, 2017). Although no significant reading growth difference was observed between implementation and comparison groups, schools that implemented with the highest scores on a measure of fidelity made better improvements on both reading and math while scores of matched comparison schools actually decreased (Choi et al, 2017). Readers seeking a broader description of specific practices under the SAM system may wish to examine the previous publication.…”
Section: Context and Purposementioning
confidence: 82%
See 3 more Smart Citations